Enhancing the Brightness of Quantum Dot Light-Emitting Diodes by Multilayer Heterostructures - Na Qiao; Zhi-Hui Chen; Yi-Biao Yang; Shao-Ding Liu; Yun-Cai Wang; Han Ye (IEEE Photonics Journal, 2016)
Quantum dots (QDs) show great promise for use in nanotechnology, owing to their high quantum efficiency, color tenability, narrow emission, and high luminescence efficiency. As a new generation of light-emitting devices (LEDs), QD-LEDs have attracted a great deal of attention in displays and lighting. To meet the commercial requirements, the brightness of QD-LEDs needs to be further improved. In this work, we propose multilayer heterostructures on a SiO2 substrate, which provides multiple reflective bands with the very high reflective efficiency of nearly up to 100%. Electric field distributes mostly in the superficial layer. The proposed structure provides highly multiband reflection covering the emission peaks of QDs in LEDs; hence, it can eventually enhance QDs' fluorescence and enhance the brightness of QD-LEDs. We investigate four typical emission wavelengths, mainly aiming for red QD-LEDs and infrared QD-LEDs, which correspond to the applications of displays, infrared illumination, optical communication, and so on. The total reflection bands can be adjusted according to practical requirements by tuning the thickness of every layer. One fabrication procedure can be used for different kinds of QDs or the same kind of QD with different sizes without changing their processing properties. The proposed structure has fewer flat layers compared with 1-D photonic crystals, which leads to lower cost and easier fabrications.